Arifin Siregar [Indonesia, Minister of Trade] - Siregar, Arifin (Institutional Knowledge at Singapore Management University, 2015)
Former Indonesian Trade Minister Arifin Siregar talks to DNA about his higher education in Holland and Germany, and his services as the Governor of Central Bank in Indonesia, during which handling the Pertamina crisis led to radical economic development. He presents his take on past Presidents Soekarno, Suharto, Habibie, Gus Dur, Megawati and Susilo Bambang Yudhoyono, including how corruption had occurred.